2014
DOI: 10.1016/j.breast.2014.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Different biological and prognostic breast cancer populations identified by FDG-PET in sentinel node-positive patients: Results and clinical implications after eight-years follow-up

Abstract: Our findings suggest that FDG-PET results reflect intrinsic biologic features of primary BC tumors and have prognostic value with respect to nodal metastases. FDG-PET false negative cases appear to identify less aggressive indolent metastases. The possibility to identify a subgroup of N+ BC patients with an outcome comparable with N- BC patients could reduce the surgical and adjuvant therapeutic intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In present study, we found aspirin’s ability to decrease the SUV max of primary CRC lesions, while demonstrated no prognostic information from SUVmax of the primary lesions. Despite some researchers have suggested that FDG-PET have prognostic value for some types of malignancies [45] , [46] , [47] , past studies were mainly focused on stage IV CRC [48] . Our study included only resectable CRC and is consistent with results from Lee.JE [49] .…”
Section: Discussionmentioning
confidence: 99%
“…In present study, we found aspirin’s ability to decrease the SUV max of primary CRC lesions, while demonstrated no prognostic information from SUVmax of the primary lesions. Despite some researchers have suggested that FDG-PET have prognostic value for some types of malignancies [45] , [46] , [47] , past studies were mainly focused on stage IV CRC [48] . Our study included only resectable CRC and is consistent with results from Lee.JE [49] .…”
Section: Discussionmentioning
confidence: 99%
“…The potential of FDG-PET in operable breast cancer however is still debated. Several authors recently showed that pre-operative FDG-PET is a highly significant predictor of outcome in breast cancer [3][4][5][6][7][8][9][10][11][12]. • Explore whether there are interactions, subgroups of patients in whom FDG -PET might be more important.…”
Section: Introductionmentioning
confidence: 99%